2016
DOI: 10.1016/j.jelekin.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to isolated shoulder fatigue during simulated repetitive work. Part II: Recovery

Abstract: The shoulder allows kinematic and muscular changes to facilitate continued task performance during prolonged repetitive work. The purpose of this work was to examine changes during simulated repetitive work in response to a fatigue protocol. Participants performed 20 one-minute work cycles comprised of 4 shoulder centric tasks, a fatigue protocol, followed by 60 additional cycles. The fatigue protocol targeted the anterior deltoid and cycled between static and dynamic actions. EMG was collected from 14 upper e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 38 publications
(39 reference statements)
2
19
0
1
Order By: Relevance
“…The statistically significant correlation between these variables suggests that the function represents the muscle fatigue portion of fatigue perception well. Perception of fatigue alone may not be sensitive enough to detect all indications of myoelectric fatigue, especially during recovery conditions (McDonald et al, 2016). Using the MMFS function to quantify myoelectric fatigue in combination with perception can give a more complete analysis of fatigue development during repetitive work tasks.…”
Section: Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistically significant correlation between these variables suggests that the function represents the muscle fatigue portion of fatigue perception well. Perception of fatigue alone may not be sensitive enough to detect all indications of myoelectric fatigue, especially during recovery conditions (McDonald et al, 2016). Using the MMFS function to quantify myoelectric fatigue in combination with perception can give a more complete analysis of fatigue development during repetitive work tasks.…”
Section: Strengthmentioning
confidence: 99%
“…Upper extremity repetitive tasks are common in the workplace, and understanding upper extremity muscle activity during these tasks is of ergonomic interest. The kinematic and muscular degrees of freedom in the shoulder complex allow for multiple strategies between and within individuals to complete a functional task with the hand (McDonald, Tse, & Keir, 2016; Tse, McDonald, & Keir, 2016). Along with individual differences, differing strategies cause fatigue to develop in different muscles and at varying rates across people, making it challenging to compare multimuscle fatigue states between people by using individual muscles (Gerdle, Larsson, & Karlsson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…f) Increased forward bending, also described by Mehta et al (2014); g) Head slightly bending forward; h) Neck bending sideways; i) Decrease in body stability; j) Changing support leg (some volunteers started to feel numb legs); Evaluation of physical fatigue based on motion analysis in manual handling of loads Bernardo et al k) Stretching body and spine; l) Holding load closer to the chest during elevation in the final stages of the experiment, resulting in a less fluid movement. This shows volunteers adapted to compensate fatigued muscles, which was also concluded by McDonald et al (2016), Lee et al (2014) and Gates et al (2011); m) Increased difficulty to follow metronome rhythm;…”
Section: Posture and Behavioral Changes Recorded On Camera And Symptomentioning
confidence: 57%
“…According to literature, higher movement variability occurs with the development of muscle fatigue (Brown et al, 2016). Muscular and kinematic adaptations occur to reduce the load on the fatigued muscles (McDonald et al, 2016). Other studies concluded that fatigue-induced changes in movement strategies (Lee et al, 2014) and subjects altered their kinematic patterns significantly in response to muscle fatigue (Gates et al, 2011).…”
Section: Posture and Behavioral Changes Recorded On Camera And Symptomentioning
confidence: 99%
“…The mean age of participants ranged from 26.4 to 45 years. Two included studies only reported the age ranges of their participants (between 20 and 24 years old) (McDonald et al, 2016;Calvin et al, 2016). Most of the included studies used HR metric (19 studies), five study used skin temperature, four studies used EMG metric, and only one study used jerk metric to measure physical fatigue (Figure 2).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%